IN VITRO SHOOT INDUCTION OF GARUT (Maranta arundinacea) WITH THE ADDITION OF 2,4-D BENZYL ADENIN - Endah Wahyurini (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2020)
Arrowroot (Maranta arundinacea L.) is a type of forest tuber plant that potentially developed as a local food crop. Arrowroot tubers can be processed as chips and starches. The difficulty of getting superior varieties and seeds in relatively large quantities and uniform can be overcome by in vitro techniques. The success of tissue culture depends on the planting media, PGR, vitamins and plant genetics. The purpose of this study was to determine the effect of giving 2.4 D and BA on the growth of arrowroot explants, as well as getting the proper concentrations of 2.4 D and BA to stimulate the growth of arrowroot tubers in vitro. The study wa conducted in a laboratory with two factors Complete Random Design Method. The first factor is the 2.4 D concentration which consists of three levels, namely: 0.5 mg / L (D1), 1 mg / L (D2) and 1.5 mg / L (D3). The second factor is the concentration of BA consisting of three levels, namely: 1 mg / L (B1), 2 mg / L (B2) and 3 mg / L (B3). Variance analysis were done at 5% level. To find out there is a real difference between treatments, Duncan Multiple Range Test (DMRT) at 5% level were conducted. The results showed that the 2.4 D treatment concentration of 1 mg / L produced a greater percentage of shoot life than other treatments. Giving 2.4 D concentrations of 1 mg / L and BA 2 mg / L stimulated quicker emergence of shoots and higher shoot lengths compared to other treatments.Keyword: 2,4 D, Benzyl adenine, Maranta arundinacea, in vitro